POSS-modified PEG Adhesives for Wound Closure - Bu, Ya-zhong; Sun, Guo-fei; Zhang, Li-cheng; Liu, Jian-heng; Yang, Fei; Tang, Pei-fu; Wu, De-cheng (Chinese journal of polymer science, 2017)
PEG-related adhesives are limited in clinical use because they are easy to swell and cannot support the cell growth. In this study, we produced a series of POSS-modified PEG adhesives with high adhesive strength. Introduction of inorganic hydrophobic POSS units decreased the swelling of the adhesives and enhanced cell adhesion and growth. The in vitro cytotoxicity and in vivo inflammatory response experiments clearly demonstrated that the adhesives were nontoxic and possessed excellent biocompatibility. Compared with the sutured wounds, the adhesive-treated wounds showed an accelerated healing process in wounded skin model of the Bama miniature pig, demonstrating that the POSS-modified PEG adhesive is a promising candidate for wound closure.